« Shopping mall » et « modernisation » des villes africaines : les cas de Douala (Cameroun) et Kigali (Rwanda) - Benjamin Michelon (Ateliers d'Anthropologie)
In most African cities, the “modernization” of urban life is changing the nature of trade and is relocating shopping areas. This evolution is having an effect on markets, which now compete with a new type of commercial surface promoted by the authorities: the shopping mall. The coexistence of these two forms raises new types of questions about the spatial evolution of African cities.This article analyses this evolution, by questioning Manuel Castells’s theory of the space of flows and the space of places. This study is based on observations conducted in two Central African cities: Douala, a major economic capital that is undergoing poorly managed urban development, and Kigali, which is trying to establish a reputation as a model modern city. This comparative study makes it possible to apprehend the changes that these African cities are currently undergoing under the effect of globalization and increasing flows.